Identification of regulons modulating the transcriptional response to SARS-CoV-2 infection in humans - Padilla-Gálvez, Mónica; Arteaga-Vazquez, Leo J.; Villaseñor-Altamirano, Ana B.; Balderas-Martínez, Yalbi Itzel; Collado-Torres, Leonardo; De Las Rivas, Javier; Blanco-Melo, Daniel; Medina-Rivera, Alejandra (Frontiers in RNA Research, 2024)
The pathophysiology underlying coronavirus disease 2019 (COVID-19) across tissues and cell types upon severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection remains to be fully characterized. Diverse cellular processes have been described, including interferon (IFN) and pro-inflammatory responses and functions of ACE2 and TMPRSS2 proteins. Characterizing how transcriptional programs are activated or repressed could give us a better understanding of the disease progression; this can be better understood via gene regulatory network reverse engineering. Here, we make use of multiple publicly available transcriptional data, such as primary cells and tissue samples obtained from COVID-19 patients’ lung autopsies, to build the transcriptional regulatory networks for each condition. Our results describe the regulatory mechanisms underlying SARS-CoV-2 infection across tissues and cell lines, identifying antiviral and pro-inflammatory networks.